2020
DOI: 10.1002/cphc.202000861
|View full text |Cite
|
Sign up to set email alerts
|

Radical‐Enhanced Intersystem Crossing in a Bay‐Substituted Perylene Bisimide−TEMPO Dyad and the Electron Spin Polarization Dynamics upon Photoexcitation**

Abstract: A 4‐amino‐2,2,6,6‐tetramethyl‐1‐piperidinyloxyl (TEMPO) radical was attached to the bay position of perylene‐3,4 : 9,10‐bis(dicarboximide) (perylenebisimide, PBI) to study the radical‐enhanced intersystem crossing (REISC) and electron spin dynamics of the photo‐induced high‐spin states. The dyads give strong visible light absorption (ϵ=27000 M−1 cm−1at 607 nm). Attaching a TEMPO radical to the PBI unit transforms the otherwise non‐radiative decay of S1 state (fluorescence quantum yield: ΦF=2.9 %) of PBI unit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 100 publications
(171 reference statements)
0
27
0
Order By: Relevance
“…Interestingly, moderate to satisfactory singlet oxygen quantum yields were observed for these dyads (0.38–0.72). Nanosecond transient absorption spectroscopy shows that the triplet state lifetimes are in the range of 109.7–188.8 μs, much longer than that of the 3 PBI state produced with the heavy atom effect (0.5 μs) …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, moderate to satisfactory singlet oxygen quantum yields were observed for these dyads (0.38–0.72). Nanosecond transient absorption spectroscopy shows that the triplet state lifetimes are in the range of 109.7–188.8 μs, much longer than that of the 3 PBI state produced with the heavy atom effect (0.5 μs) …”
Section: Discussionmentioning
confidence: 93%
“…Nanosecond transient absorption spectroscopy shows that the triplet state lifetimes are in the range of 109.7−188.8 μs, much longer than that of the 3 PBI state produced with the heavy atom effect (0.5 μs). 39 The TREPR spectra of the three dyads were studied (Figure 4). Interestingly, we found the spectra are excitation-wavelength-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…20,22 It is also proposed to be one of the mechanisms of the enhanced intersystem crossing in some molecular conjugates. 11,23 It has to be noticed that the influence of the spin coherence in three-spin system was investigated earlier by Bargryansky et al 8,9 They studied the radical-ion triads in the liquid solution in the situation when one of the radicals of the singlet-born pair recombines with the encounter radical. The statistics of the recurring encounters follows a "cage effect" when two radicals that meet once have multiple collisions before they go away.…”
Section: ■ Quantum Yieldmentioning
confidence: 99%
“…Because of the nonequality of these interactions, the sing-doublet and trip-doublet states () become mixed, and this promotes the depopulation of the excited sing-doublet state. It has been shown that this mechanism is responsible for the decrease of the lifetime of the excited sing-doublet state in the photoexcited paramagnetic porphyrins. , It is also proposed to be one of the mechanisms of the enhanced intersystem crossing in some molecular conjugates. , …”
Section: Quantum Yieldmentioning
confidence: 99%
“…Soon afterward, Li et al demonstrated a stable radical photosensitizer (NDI-TEMPO) by covalently linking TEMPO with NDI, as shown in Figure 7B. [36] NDI-TEMPO demonstrated high triplet state quantum yield (Φ T = 74 %), a longlived triplet state (τ = 8.7 μs), and fast ISC (1/K EISC = 338 ps), which is beneficial for improving the 1 O 2 generation efficiency. Strong emissive (E) polarization was firstly observed in D 0 state of the TEMPO moiety owing to the quenching of the excited singlet state of NDI by the radical moiety.…”
Section: Nitroxidementioning
confidence: 99%